Antimitotic Activity of Cayratia trifolia Ethanol Extract on Zygote Cells of Tripneustes gratilla - Eva Feriadi; Wahyuni Wahyuni; Muhammad I. Yusuf (Pharmacology and Clinical Pharmacy Research)
Cancer is a devastating disease characterized by abnormal cell growth. Due to several safety issues associated with current cancer treatment, identification of new strategies for cancer therapy is considered necessary. Natural substances in plants m and fruits have the potentials to be developed as anticancer drugs. One of them is Cayratia trifolia (C. trifolia). This study was aimed to determine the cytotoxic activity of stem and leaf ethanol extract of C. trifolia against zygote cells of sea urchin or Tripneustes gratilla (T. gratilla). Extraction of stem and leaf of C. trifolia was conducted using maceration method in ethanol solvent. Thin layer chromatography was performed to screen phytochemicals contained in the extract. Zygoteof T. gratilla was used to conduct antimitotic activity test. We found that stem and leaf ethanol extract had IC50 of 169.82 μg/ml and 208.92 μg/ml, respectively. In comparison with positivecontrol of vincristine which had IC50 value of 3.23x10-3 μg/ml (very strong category), this extract showed moderate antimitotic activity. In conclusion, C. trifolia is potential to be developed as anticancer treatment.Keywords: cancer, Cayratia trifolia, antimitotic